Optimal water management in small-scale tank irrigation systems - Unami, K.; Kawachi, T.; Yangyuoru, M. (Energy, 2005)
The small-scale tank irrigation system is an effective option for sustainable agricultural water development. The management strategy for water release in such a system is considered in the framework of variational calculus. A minimum principle is deduced to characterize an optimal strategy minimizing a performance index that evaluates water content deviation in the command area and the time when the irrigation tank dries up. The optimal strategies are demonstrated in two practical example systems. © 2004 Elsevier Ltd. All rights reserved.